PREDICTING INNOVATION PERFORMANCE AS A FUNCTION OF TALENT MANAGEMENT: THE ROLE OF SELF-EFFICACY AND SYSTEM EMBEDDEDNESS OF KNOWLEDGE - Dr. Attaullah; Dr. Zubair Alam Khan; Dr. Abdul Wasia; Dr. Misbah Noor; Dr.Sadaf Naushad (Review Journal of Social Psychology & Social Works, 2024)
Modern-day organizations work in an extremely competitive environment, wherein invention and innovation constantly affect business activities. This vibrant environment is extremely challenging, and organizations must pay due attention to invention and innovation for survival. Organizations with high innovation performance remain competitive and stay ahead of the game. One of the significant factors affecting innovation performance is talent management. Talent management practices are immensely important for an organization as they help to identify and fill the pivotal positions, through attraction, development, succession planning, and retention of talented individual. This study inspected the relationship between talent management and innovation performance considering the mediating effect of self- efficacy, and the moderating effect of system embeddedness of knowledge. The outcomes of this cross-sectional study show that talent management is positively associated with innovation performance. Likewise, self-efficacy mediated the relationship between talent management and innovation performance. Moreover, the system embeddedness of knowledge is found to have a moderating effect by strengthening the said relationship. The study provides viable strategic recommendations for improving innovation performance. It also offers new insights into the literature of talent management, and provides significant theoretical, methodological, and practical implications.